Assesment Sistem Informasi Manajemen Rekam Medis pada Klaim Rawat Jalan BPJS dengan Health Metric Network - Kristiawan, Hedie; Parulian, Adi Anggoro; Firmansyah, Yura Witsqa; Prasaja, Bhisma Jaya (Lontara Journal of Health Science and Technology, 2025)
Health information systems are a priority in supporting Universal Health Coverage (UHC). Yet 65% of WHO member states face challenges in health information system integration, causing losses of up to $300 billion per year. In Indonesia, 35% of BPJS claims are delayed due to incomplete documentation. This study aims to evaluate the Medical Record Management Information System (SIMRM) at West Bandung Private Hospital using the Health Metric Network (HMN) framework. The mix method design was used with a total sampling of 22 medical record staff. Data was collected through questionnaires, interviews and observations. The results show that SIMRM is in the category of "there is but inadequate" with a percentage of 59%. The evaluation showed weaknesses in the completeness of documentation and the accuracy of the diagnostic code. So it can be concluded that even though SIMRM helps speed up the documentation process, improvements are still needed in system integration and staff training to increase the effectiveness of outpatient BPJS claims, so that it can improve the quality of health services.